The unique benefits of electro-hydraulic pulse technology of drilling wells - Stoev, M.; Kusaiynov, K.; Shuyushbaeva, N.N.; Turdybekov, K.M; Ahmadiev, B.A. (Publishing House of the KarSU named after E.A.Buketov, 2014)
The aim of the study is to develop scientific and practical principles of implementation of energy saving heat pump technology for heat and cold supply to residential, public and industrial premises on the basis of alternative and renewable sources of energy. One of the effective methods to generate heat from groundwater by means of heat pump technology is the use of wells for consolidation of heat exchange elements produced by drilling. Fundamentally new innovative method of making wells is electro-hydraulic drilling. According this method an electrical energy transformed into mechanical energy of shock waves that can break up rocks directly in the bottom hole. This paper describes the results of a study of the electric hydro-pulse effect on hard and super hard rock minerals.
Keywords: heat pump; heat exchanger; renewable sources of energy; groundwater; well; electro-hydraulic drilling